Mudanças de políticas e (des) mobilizaç\~ao de capacidades estatais: O caso do cadastro único - Denise do Carmo Direito; Natália Massaco Koga; Elaine Cristina Licio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This study aimed to trace the chain of relationships between contextual factors and built capacities in order to understand the process of transformations that have impacted the Single Registry for Social Programs (Cadastro Único para Programas Sociais - Cadastro Único) since its creation in 2001. Movements of expansion and retraction of this instrument were identified, mapping the mobilization and demobilization of state capacities that produce, reproduce, stabilize, and destabilize legacies arising from political and institutional changes. The analysis allowed us to reconstitute the trajectory of the Cadastro in four major periods of transformations (policy changes), namely: the shortest one from 2001-2002 reflects its creation; 2003-2015 brings its expansion, consolidation, and qualification of the cadastral data; 2016-2018 portrays the funding crisis and change in management focus; the fourth period is related to the crisis arising from the covid-19 pandemic and is still open. The research revealed that the Single Registry went through different expansion movements until 2016, when trends of retraction and demobilization, or even redirection of capacities began to be identified, especially with regard to its role of interfederative and intersectoral integration. Since 2019, there are possibilities of dismantling, in a scenario of uncertainty and growing demand for social protection.
10419/284884
Keywords: I38; D73; 330; Single Registry for Social Programs; policy change; policy dismantling; state capacities